Effect of gelling agents on the techno-functional, collagen bioavailability and phytochemical properties of botanic gummy jelly containing marine hydrolyzed collagen - Yu Bin Lam; Anis Syafiqah Yusri; Norizah Mhd Sarbon (Food Chemistry Advances)
The trend of incorporating traditional herbal medicine, also known as Jamu, to enhance gummy jelly quality in terms of taste, texture, and nutritional properties. This study developed the botanic gummy jelly using different ratios of pectin and gelatin as gelling agents, along with 3% (w/v) of 'Jamu' in constant amounts (3 mL) for each formulation and marine collagen, to determine its techno-functional, collagen bioavailability, and phytochemical properties. The different pectin-to-gelatin ratios were presented as Formulations A (0:10), B (0.5:9.5), C (1:9), D (1.5:8.5), and E (2:8). The results show that the increased pectin-to-gelatin ratio significantly increased the water activity, moisture content, and total soluble solids. In contrast, the pH value, hardness, gumminess, and chewiness decreased. The different pectin-to-gelatin ratios also influenced the gummy jelly's rheological properties. In terms of phytochemical contents, the total phenolic (1.80–2.54 mg GAE/g gummy), flavonoid (0.16–0.42 mg QHE/g gummy), and tannin (10.87–71.83 mg TAE/g gummy) were decreased with the increased pectin to gelatin ratio. This study proved that an increased pectin-to-gelatin ratio improved botanic gummy jelly's techno-functionality, and collagen bioavailability.